2016
DOI: 10.1021/acscatal.6b02773
|View full text |Cite
|
Sign up to set email alerts
|

Carbonylation of Ethylene Oxide to β-Propiolactone: A Facile Route to Poly(3-hydroxypropionate) and Acrylic Acid

Abstract: We report an improved synthesis of poly­(3-hydroxypropionate) (P3HP) from ethylene oxide (EO) and carbon monoxide (CO) through the intermediate β-propiolactone (PL). The optimized carbonylation of EO resulted in high selectivity for PL using a bimetallic [Lewis acid]+[Co­(CO)4]− catalyst. Anionic ring-opening polymerization of PL by organic ionic compounds to afford P3HP was also investigated. A phosphazenium carboxylate initiator displays the highest activity for the polymerization and produces polyesters wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 52 publications
1
49
0
Order By: Relevance
“…Carbon monoxide is known to be an intermediate of CO 2 reduction on copper electrodes in aqueous electrolytes [21][22] as well as in acetonitrile electrolyte containing small amounts of water. [23] However, the absence of the band at 1800 cm À 1 (corresponding with propylene carbonate) when CO 2 is exchanged for CO, discards CO as the electroactive species in the mechanism of propylene carbonate formation. [23] However, the absence of the band at 1800 cm À 1 (corresponding with propylene carbonate) when CO 2 is exchanged for CO, discards CO as the electroactive species in the mechanism of propylene carbonate formation.…”
Section: Proposed Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon monoxide is known to be an intermediate of CO 2 reduction on copper electrodes in aqueous electrolytes [21][22] as well as in acetonitrile electrolyte containing small amounts of water. [23] However, the absence of the band at 1800 cm À 1 (corresponding with propylene carbonate) when CO 2 is exchanged for CO, discards CO as the electroactive species in the mechanism of propylene carbonate formation. [23] However, the absence of the band at 1800 cm À 1 (corresponding with propylene carbonate) when CO 2 is exchanged for CO, discards CO as the electroactive species in the mechanism of propylene carbonate formation.…”
Section: Proposed Mechanismmentioning
confidence: 99%
“…[17] It is also known that the catalytic reaction between CO and propylene oxide can yield propiolactone under certain conditions. [23] However, the absence of the band at 1800 cm À 1 (corresponding with propylene carbonate) when CO 2 is exchanged for CO, discards CO as the electroactive species in the mechanism of propylene carbonate formation. Previous studies of CO 2 reduction in non-aqueous solvents showed that the main products formed at high overpotentials are bi(carbonates).…”
Section: Proposed Mechanismmentioning
confidence: 99%
“…However, poly(3HP) was not commercially feasible to produce in large quantities because β-propiolactone as a substrate has carcinogenic properties ( Dunn, 2012 ; Dunn et al, 2016 ). 3-HP, which has low crystallinity, is an ideal precursor that forms a constituent for several copolymers like poly(3-hydroxybutyrate-co-3-hydroxypropionate) [poly(3HB-co-3HP)] or poly(3-hydroxypropionate-co-4-hydroxybutyrate) [Poly(3HP-co-4HB)] ( Zhou et al, 2011 ; Wang et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 44 ] In 2016, Coates and co‐workers investigated various catalysts for the Novomer route. [ 45 ] Ethylene oxide and carbon monoxide can be derived from fossil resources or respectively from bioethanol and CO 2 or gasified biomass, making it virtually a biobased route. Similarly, poly(3‐hydroxybutyrate) (PHB), biosynthesized by various microorganisms from wastewater, can be pyrolyzed to crotonic acid (CrA) (see Section 2.5.4) for more details).…”
Section: Production Of Biobased Acrylates and Analogsmentioning
confidence: 99%